Narwhal's sweet tooth - Clanton, Ben, 1988- (Clanton, Ben, 1988- Narwhal and Jelly book, 2024)
"In the hilarious ninth book of this blockbuster graphic novel series, Narwhal and Jelly learn a thing or two about tusk-tooth dental hygiene . . . and feelings! Everyone knows that Narwhal is a big fan of sugary treats - but Jelly is shocked when Narwhal's tusk-tooth isn't looking so pearly white anymore. Thankfully, no one knows more about dental hygiene than Shark - he has seven rows of teeth, after all! Meanwhile, Jelly and Crab try to teach Narwhal that it's fine to frown if you're feeling down. Can Narwhal's friends convince the happiest creature in the ocean that it's okay to be upset?"--